How to train your myeloid cells: a way forward for helminth vaccines? - Doolan, Rory; Putananickal, Namitha; Tritten, Lucienne; Bouchery, Tiffany (Frontiers in Immunology, 2023)
Soil-transmitted helminths affect approximately 1.5 billion people worldwide. However, as no vaccine is currently available for humans, the current strategy for elimination as a public health problem relies on preventive chemotherapy. Despite more than 20 years of intense research effort, the development of human helminth vaccines (HHVs) has not yet come to fruition. Current vaccine development focuses on peptide antigens that trigger strong humoral immunity, with the goal of generating neutralizing antibodies against key parasite molecules. Notably, this approach aims to reduce the pathology of infection, not worm burden, with only partial protection observed in laboratory models. In addition to the typical translational hurdles that vaccines struggle to overcome, HHVs face several challenges (1): helminth infections have been associated with poor vaccine responses in endemic countries, probably due to the strong immunomodulation caused by these parasites, and (2) the target population displays pre-existing type 2 immune responses to helminth products, increasing the likelihood of adverse events such as allergy or anaphylaxis. We argue that such traditional vaccines are unlikely to be successful on their own and that, based on laboratory models, mucosal and cellular-based vaccines could be a way to move forward in the fight against helminth infection. Here, we review the evidence for the role of innate immune cells, specifically the myeloid compartment, in controlling helminth infections. We explore how the parasite may reprogram myeloid cells to avoid killing, notably using excretory/secretory (ES) proteins and extracellular vesicles (EVs). Finally, learning from the field of tuberculosis, we will discuss how anti-helminth innate memory could be harnessed in a mucosal-trained immunity-based vaccine.